The Role And Impact Of Religion On The Architecture Of Mosques And Churches - Salimi, Amineddin; Yurtyapan Salimi, Aysegul; Kara Pilehvarian, Nuran (The Turkish Online Journal of Design Art and Communication, 2016)
Art has been included customary and possible dimensions to speak by man with holiness, before when was related to the veil of human's egotism. In this age, since the dimension was not sourced from right and truth for man and good names of providence did not come to seek the veil of idolatrous, symbols and motifs appear the occult meanings and themselves are showy of theological facts. The art can appear as religion, because from our sight of principle of knowledgeable, art and religion are intertwined naturally. Every ingenious demonstrate the mysteries that don’t appear except with brightness of intellectuality, and it is for having a share of the divine realm, which is the agency cause of manifesting artistic works. The ingenious should attract to the truth to create the making clear beautiful faces by assisting God diffusion. Ingenious lives in the shadow of the verbal knowledge tree. In this sense, if we look closely, we can find very similarities between religious and artistic knowledge: knowledge of art is as immediate and direct as religious knowledge. In the knowledge of art, the reason was not discussed as well acquired knowledge. Therefore, in this study, we investigate the religious influence on architecture, especially on the architecture of religious buildings such as churches and mosques.
Keywords: Islamic art; Christian art; Religion; Architecture; Mosque; Church; İslam sanatı; Hıristiyan sanat; Din; Mimarlık; Cami; Kilise